2018
DOI: 10.1111/iej.12991
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Reciproc Blue in removing canal filling material and regaining apical patency

Abstract: Both M-Wire Reciproc and Reciproc Blue instruments were effective in removing filling materials from oval-shaped straight canals. Apical patency was reestablished in all specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 29 publications
5
41
0
Order By: Relevance
“…De‐Deus et al . () reported that both M‐Wire Reciproc and Reciproc Blue instruments were effective in removing filling materials with no significant differences between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…De‐Deus et al . () reported that both M‐Wire Reciproc and Reciproc Blue instruments were effective in removing filling materials with no significant differences between them.…”
Section: Discussionmentioning
confidence: 99%
“…De‐Deus et al . () reported that instrumentation with R40 after R25, for both M‐Wire Reciproc and Reciproc Blue had a significant effect on the removal of filling material. M‐Wire Reciproc and Reciproc Blue are one‐file systems for root canal preparation but, in the present study, two files (R25 and R40) were used for minimization of residual filling materials in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that hand, rotary and reciprocating files are incapable of completely removing all filling material from the root canal during retreatment procedures (Somma et al 2008). This is regardless of whether the root canal is straight (Marfisi et al 2010, Crozeta et al 2016, Canali et al 2019, Delai et al 2019), oval (Bago et al 2019, De‐Deus et al 2019a) or curved (Marfisi et al 2015, Crozeta et al 2016). According to several studies, approximately 10–49% of root canal walls remain uninstrumented as a result of rotary and reciprocating instrumentation (Gambill et al 1996, Siqueira et al 2013, Zhao et al 2014, Drukteinis et al 2019, De‐Deus et al 2019b).…”
Section: Introductionmentioning
confidence: 99%